Temperature Preference and Sex Differentiation in African Catfish, Clarias gariepinus. Issue 1 (1st March 2017) - Santi, Saïdou; Rougeot, Carole; Toguyeni, Aboubacar; Gennotte, Vincent; Kebe, Ibrahima; Melard, Charles
GRAPHICAL ABSTRACT: (1) African catfish larvae moved spontaneously through a thermal continuum from lower (28°C) to higher (32 and 36.5°C) temperatures during the sex differentiation period. (2) Thermal preference is highly variable and differed according to progeny and early life periods (before, during, and after high thermosensitive period). (3) Displacements in a thermal continuum system resulted in masculinization in all tested progenies. ABSTRACT: The African catfish Clarias gariepinus has a genetic sex determination system in which high temperature induces masculinization. The thermosensitive period for sex differentiation is short and occurs very early (from 6 to 8 days posthatching [dph]). As young juveniles can encounter high masculinizing temperature (36.5°C) in African water points, we aimed to determine the thermal preference of sexually undifferentiated juveniles and investigate if they spontaneously move toward high masculinizing temperature. Experiments were carried out in an environmental continuum (28–28–28°C and 28–32–36.5°C) made up of three 50‐L aquariums connected together. Four hundred larvae from 10 different full‐sib progenies were reared successively from 2 to 14 dph in these facilities. Before and after thermal treatments, fish were reared at 28°C until sex ratio determination at 70 dph. In the control continuum, fish were nearly equally distributed in the three compartments. Conversely, in the thermal continuum, compartment occupation significantly differed with progeny and period. During the highly thermosensitive period, two of five progenies significantly preferred (54.7% and 39.8% occupation) the 36.5°C compartment. All tested progenies reared in thermal continuum and separated 36.5°C aquarium showed a skewed sex ratio toward the male phenotype (78–100%). Nevertheless, no correlation was found between 36.5°C compartment occupation and sex ratio in thermal continuum groups. As masculinization temperature could be encountered in African water points during the spawning season, we discussed the adaptive advantage for the African catfish to display a sex differentiation process controlled by a temperature effect.